Ratio of Early to Late Type Stars in SMC Clusters - Kontizas, E.; Kontizas, M.; Dapergolas, A.; Hatzidimitriou, D. (The Harlow-Shapley Symposium on Globular Cluster Systems in Galaxies, 1988)
Spectral classification of stars in SMC clusters provide useful information on the evolutionary history of this galaxy and permit to test the theory of stellar evolution.